Economic Exchange or Gender Identities? Housework Division and Wives' Economic Dependency in Different Contexts. (2nd October 2020) - Mandel, Hadas; Lazarus, Amit; Shaby, Maayan
Abstract: This paper explores cross-country variation in the relationship between division of housework and wives' relative economic contribution. Using ISSP 2012 data from 19 countries, we examined the effect of two contextual factors: women's employment rates, which we link to economic exchange theories; and gender ideology context, which we link to cultural theories. In line with economic-based theories, economic exchange between housework and paid work occurs in all countries—but only in households which follow normative gender roles. However, and consistent with the cultural-based theory of 'doing gender', wives undertake more housework than their spouses in all countries—even if they are the main or sole breadwinners. This universal gendered division of housework is significantly more salient in more conservative countries; as the context turns more conservative, the gender gap becomes more pronounced, and the relationship between paid and unpaid work further removed from the economic logic. In gender egalitarian societies, in contrast, women have more power in negotiating housework responsibilities in non-normative gender role households. In contrast to gender ideology, the cross-country variations in women's employment did not follow the expectations that derive from the economic exchange theory.